HUBUNGAN POLA ASUH ORANG TUA DENGAN PRESTASI BELAJAR ANAK USIA SEKOLAH DI SDN STANDAR NASIONAL KAYU PUTIH 09 PAGI JAKARTA TIMUR TAHUN 2011 - Rina, Tetty (Jurnal Kesehatan AYURVEDA, 2012)
ABSTRACTÂ The family is the first place where children receive parenting. Various types of parenting are used by family that is authoritative, permissive, authoritharian. Parenting be applied by a parents to children will contribute especially to the field of education. Success or failure of the educational process can be observed by the high and low student achievement, especially in children of school age, because at this time the child requires a value (numeric report) is good, without considering whether his performance deserved or not rated. This study uses a descriptive design with cross sectional correlation. Sampling techniques used in this study was non random sampling using purposive sampling method, sampling technique based on a specific considerations made by the researcher himself. Obtained that parenting parents with learning achievement children of school age grade 2 and 3 were 52 respondents. The majority of high academic achievemnt (â¥ 86) were 31 (59,6%) respondents with authoritative parenting parents were 39 (75%), permissive parenting parents were 5 (9,6%) and authoritharian parenting parents were 8 (15,4%) respondents. The result of the analysis show that there is a relationship parenting parents with learning achievement in children of school age grade 2 and 3 (p value = 0,038) with a significance value smaller than the of Î± = 0,05 so with this we can conlude that H0 is rejected so that there is a relationship parenting parents with learning achievement in children af school age grade 2 and 3 in Elementary School Standart National Kayu Putih 09 Pagi Jakarta Timur in 2011.Â Keyword: Parenting Parents, Learning Achievement, Children Of School AgeÂ